Mewujudkan Pembelajaran yang Inovatif di Madrasah melalui Pelatihan Portofolio Berbasis HOTS - Edy Herianto; M. Ismail; Dahlan Dahlan; M. Mustari; Sawaludin Sawaludin (Jurnal Gema Ngabdi, 2023)
Madrasah is an Islamic religious education unit under the auspices of the Ministry of Religion. In Kota Mataram, Provinsi NTB, there are two types of madrasas: public and private. Based on the interviews with PPKn teachers at the madrasah, there was anxiety about PPKn teachers carrying out learning. The reason is that students are less interested in participating in the learning, considering the implementation of education, which tends to be monotonous and based on low-level thinking skills (LOTS). PPKn teachers have realized this but have not made many innovations due to limited knowledge and experience in developing innovative learning. Based on this, the purpose of this community service is to realize innovative PPKn learning in madrasas through HOTS-based portfolio learning training. The method used is guided training and mentoring. The implementation stages of the method include preparation, training, and guided assistance. The results show that there has been an increase in participants' cognitive abilities regarding HOTS-based learning after attending the training. In addition, participants have been able to develop innovative PPKn learning designs, which include a HOTS-based portfolio approach.